#TITLE_ALTERNATIVE# - FAJAR SIDIK (NIM 10102023); Pembimbing: Dr. Djoko Suprijanto, M.
Hamming weight enumerator is a 2 variables polynomial containing information about the weight distribution of codewords of a linear code. It is known that for a binary self-dual code with all weights divisible by 4, its Hamming weight enumerator is unchanged (or invarian) under the action of a group of order 192 and belong to a spesific ring of invariant (MacWilliams dan Sloane, 1977). In this final project, we investigate a structure of invariant ring to which the Hamming weight enumerators belong for self-dual codes over Fq using invariant theory.